Remote Working in a Public Bureaucracy: Redeveloping Practices of Managerial Control When Out of Sight - Hartner-Tiefenthaler, Martina; Goisauf, Melanie; Gerdenitsch, Cornelia; Koeszegi, Sabine T. (Frontiers in Psychology, 2021)
This article examines managerial control practices in a public bureaucracy at the moment of introducing remote work as part with a new ways of working (NWW) project. The qualitative study builds on 38 interviews with supervisors and subordinates conducted before the advent of COVID-19. By interpreting interviewees’ conversations about current and anticipated future work practices in the changing work setting, we reveal tacit and hidden practices of managerial control that are currently prevalent in many organizations introducing remote working. Three constitutive moments of the organization’s transformation to NWW are analytically distinguished: (i) how implicit becomes explicit, (ii) how collective becomes self, and (iii) how personal becomes impersonal. Our findings emphasize that the transition to NWW must take into account prevailing institutional logics and must reconnect to a fundamental and often neglected question: What does doing work mean within the particular organization? Negotiating this fundamental question might help to overcome supervisors’ uncertainties about managerial control and provide clarity to subordinates about what is expected from them while working remotely. Finally, we discuss how the transition to NWW may serve as both an opportunity and a potential threat to established organizational practices while highlighting the challenge supervisors face when the institutional logics conflict with remote working.